Building trusting relationships to support implementation: A proposed theoretical model - Metz, Allison; Jensen, Todd; Farley, Amanda; Boaz, Annette; Bartley, Leah; Villodas, Melissa (Frontiers in Health Services, 2022)
This paper presents a theory of change that articulates (a) proposed strategies for building trust among implementation stakeholders and (b) the theoretical linkages between trusting relationships and implementation outcomes. The theory of change describes how trusting relationships cultivate increases in motivation, capability, and opportunity for supporting implementation among implementation stakeholders, with implications for commitment and resilience for sustained implementation, and ultimately, positive implementation outcomes. Recommendations related to the measurement of key constructs in the theory of change are provided. The paper highlights how the development of a testable causal model on trusting relationships and implementation outcomes can provide a bridge between implementation research and implementation practice.